The syntax of sentential stress - Kahnemuyipour, Arsalan (Oxford : Oxford University Press, 2009)
This book explores the nature of sentential stress, how it is assigned and its interaction with information structure. Its central thesis is that the position of sentential or nuclear stress is determined syntactically and that cross-linguistic differences in this respect follow from syntactic variations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Accents and accentuation; Grammar, Comparative and general -- Sentences; Emphasis (Linguistics); Oral communication